Prevention of postoperative capsular bag opacification using intraocular lenses and endocapsular devices maintaining an open or expanded capsular bag. Issue 3 (March 2016) - Kramer, Gregory D.; Werner, Liliana; Mamalis, Nick
Abstract : N/A: Postoperative capsule opacification is a multifactorial physiological consequence of cataract surgery that remains the most common complication of this procedure. A literature review that included several intraocular lenses (IOLs) and endocapsular devices studied in our laboratory found that devices maintaining the capsular bag in an open or expanded state were associated with improved bag clarity. This observed effect likely occurs secondary to the complex interactions of myriad mechanisms, which include formation of a barrier to lens epithelial cell (LEC) migration, mechanical compression of residual LECs, mechanical stretch at the level of the capsule equator, maintenance of overall bag contour, and enhanced endocapsular circulation of aqueous humor. We review the designs of endocapsular devices and IOLs that minimize the degree of postoperative capsule opacification by preventing capsular bag collapse and discuss the underlying mechanisms that contribute to this phenomenon. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.